Methodological considerations on the relationship between the 1,500-m rowing ergometer performance and vertical jump in national-level adolescent rowers - Maciejewski, H.; Rahmani, A.; Chorin, F.; Lardy, J.; Samozino, P.; Ratel, S. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to investigate whether 3 different approaches for evaluating squat jump performance were correlated with rowing ergometer performance in elite adolescent rowers. Fourteen young male competitive rowers (15.3 ± 0.6 years), who took part in the French rowing national championships, performed a 1,500-m all-out rowing ergometer performance (P1500) and a squat jump (SJ) test. The performance in SJ was determined by calculating the jump height (HSJ in cm), a jump index (ISJ = HSJ·body mass·gravity, in J), and the mean power output (PSJ in W) from the Samozino et al.'s method. Furthermore, allometric modeling procedures were used to consider the importance of body mass (BM) in the relationships between P1500 and jump scores. P1500 was significantly correlated with HSJ (r2 = 0.29, p = 0.05), ISJ (r2 = 0.72, p < 0.0001), and PSJ (r2 = 0.86, p < 0.0001). Furthermore, BM explained at least 96% of the relationships between SJ and rowing performances. However, the similarity between both allometric exponents for PSJ and P1500 (1.15 and 1.04, respectively) indicates that BM could influence jump and rowing ergometer performances at the same rate, and that PSJ could be the best correlate of P1500. Therefore, the calculation of power seems to be more relevant than HSJ and ISJ to (a) evaluate jump performance and (b) infer the capacity of adolescent rowers to perform 1,500-m all-out rowing ergometer performance, irrespective of their body mass. This could help coaches to improve their training program and potentially identify talented young rowers.